Critical Edition and Philological Analysis of Isa 49–50 based on Coptic Manuscript sa 52 (M 568) and Other Coptic Manuscripts in the Sahidic Dialect and the Greek Text of the Septuagint - Bąk, Tomasz Bartłomiej (The Biblical Annals, 2023)
The following article constitutes a critical edition, translation and philological analysis of Isa 49–50 based on Coptic manuscript sa 52 and other available manuscripts in the Sahidic dialect. The first part outlines general information about the section of codex sa 52 (M 568) that contains the analysed text. This is followed by a list and brief overview of other manuscripts featuring at least some verses from Isa 49–50. The main part of the article focuses on the presentation of the Coptic text (in the Sahidic dialect) and its translation into English. The differences identified between the Sahidic text and the Greek Septuagint, on which the Coptic translation is based, are illustrated in a tabular form. It includes, for example, additions and omissions in the Coptic translation, lexical changes and semantic differences. The last part of the article aims to clarify more challenging philological issues observed either in the Coptic text itself or in its relation to the Greek text of the LXX.